Pengembangan Media Kartu Kata untuk Memfasilitasi Kemampuan Membaca Permulaan Peserta Didik Kelas I di SDN 138 Basokeng Kab. Bulukumba - Ainun Mutmainnah; Andi Halimah; Umar Sulaiman (Prodi PGMI IAI Sahid, 2023)
This study aims to produce a word card media product to facilitate the studentsp starting reading ability in grade I SDN 138 Basokeng which is valid, practical, and effective. This research is a type of research and development or Research and Development (R&D), this research is used to produce products and test the effectiveness of these products. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Based on the results of limited trials conducted, the level of validity of the word card media obtained the results of material expert validation with an average of 3.83 being in the very valid category, because 3,5 ≤ V ≤ 4 so that the material on the media was said to be very valid, while the results media expert validation with an average of 4.00 is in the very valid category, because 3,5 ≤ V ≤ 4 so that the word card media is said to be very valid. The level of practicality of the word card media is said to be practical because the learning media is assessed by the teacher using a teacher response questionnaire with an average of 3.53. The level of effectiveness of word card media on preliminary reading material is categorized as effective, because 92% of students (13 people) get a value greater than or equal to the KKM value with an average value of 94.53.